Combination of the Distance From Tumor Edge to Subventricular Zone and IDH Mutation Predicts Prognosis of Patients With Glioma - Zhang, Shuixian; Zhao, Fengchun; Zhou, Tengyuan; Liu, Dan; Yao, Xiaohong; Fu, Wenjuan; Liu, Zhi; Lan, Chuan; Lai, Zhaopan; Liu, Chen; Li, Haitao; Li, Yuhong; et al. (Frontiers in Oncology, 2021)
Both subventricular zone (SVZ) contact and isocitrate dehydrogenase 1 (IDH1) mutation have been reported to be related to the outcome of glioma, respectively. However, far too little attention has been paid to the role of tumor edge-SVZ distance in the outcome of glioma. We aim to assess the value of tumor-SVZ distance, as well as combined tumor-SVZ distance and IDH status, in predicting the outcome of gliomas (WHO grade Ⅱ-Ⅳ). Here, the MR images and clinical data from 146 patients were included in the current study. The relationship between survival and the tumor-SVZ distance as well as survival and combination of tumor-SVZ distance and IDH status were determined via univariate and multivariate analysis. In univariate analysis of tumor-SVZ distance, the patients were divided into three types (SVZ involvement, tumor-SVZ distance from 0 to 10 mm, and tumor-SVZ distance > 10 mm). The results showed that the OS (p = 0.02) and PFS (p = 0.002) for the patients had a positive correlation with the tumor-SVZ distance. In addition, simple linear correlation found a significant relationship between the two parameters (OS and PFS) and tumor-SVZ distance in patients with non SVZ-contacting glioma. Combination analysis of the tumor-SVZ distance and IDH status showed that IDH1-mutation and SVZ non-involvement enable favorable outcomes, whereas IDH1-wild type with SVZ involvement indicates a significantly worse prognosis in all patients. Moreover, in patients with non SVZ-contacting glioma, IDH1-mutation concurrent with tumor-SVZ distance > 10 mm has better OS and PFS. IDH1-wild type and tumor-SVZ distance from 0 to 10 mm suggest poorer OS and PFS. Multivariate analysis showed WHO grade Ⅳ, SVZ involvement, tumor-SVZ distance from 0 to 10 mm, IDH1-mutation, gross total resection and chemotherapy serve as independent predictors of OS. WHO grade Ⅳ, SVZ involvement, tumor-SVZ distance from 0 to 10 mm, IDH1-mutation and chemotherapy serve as independent predictors of PFS of patients with glioma. In conclusion, tumor-SVZ distance and IDH1 mutation status are the determinants affecting patient outcome.